INTEGRASI PAJAK DAN ZAKAT SEBAGAI SUMBER PEMBIAYAAN PEMBANGUNAN NASIONAL - Nur Hadiyati (Legality : Jurnal Ilmiah Hukum, 2018)
The state in carrying out his duties to achieve public welfare requires the costs described in the budget of state income and expenditure (APBN). Taxes are Indonesia's largest source of revenue, but currently have decreased. The government is aware of the potential of zakat as a source of national development financing. Then the idea emerged to integrate tax and zakat withdrawal. This study aims to provide an understanding regarding the formulation of the integration of tax and zakat starting from definition of tax and zakat, the use of tax and zakat, the institutional structure that is authorized to collect tax and zakat. The method used in this journal is normative legal research with primary and secondary legal material sources. There are three models with regard to the integration of zakat and taxes offered: (1) zakat and tax payments are two different things and cannot be put together; (2) the payment of zakat releases the obligation to pay taxes; and (3) zakat payments provide a reduction in the burden of tax payments. Integration of tax and zakat requires in-depth study.